(untitled) (Homoeopathy for All, 2026)
Dandruff is a common scalp disorder, affects aesthetic value and often causes itching. Dandruff is the term used to describe simple scaling of the skin on the scalp. Dandruff is a common condition that causes small pieces of dry skin to flake from the scalp. It isn’t contagious or harmful. But it can be embarrassing and difficult to treat. The word dandruff (dandruff, dandriffe) is of Anglo-Saxon origin, a combination of ‘tan’ meaning ‘tetter’ and ‘drof’ meaning ‘dirty’. This article provides an overview of the aetiology, diagnosis, and appropriate general & homoeopathic management of this disorder.